IMPLEMENTASI PENDEKATAN GENRE-BASED APPROACH DALAM PEMBELAJARAN MENULIS CERPEN DI MATA PELAJARAN BAHASA INDONESIA KELAS III DI MIS NURUL HIKMAH PAMEKASAN MADURA - Qurratul Aini; irwan setia budi irwan; Werdining Wulan (Akademika: Jurnal Keagamaan dan Pendidikan, 2024)
Students' writing ability is an important aspect of language skills in Indonesian Language Education. This research aims to describe how to implement the GBA approach in studying short story writing in the Indonesian language field for class 3 MIS Nurul Hikmah Madura. The method used is qualitative with descriptive methods. This research uses primary data and secondary data. Data collection was carried out using three methods, namely observation, interviews and documentation. The results of this research explain that the genre-based approach used in learning to write short stories is that the teacher makes a lesson plan first. In learning activities, the teacher explains the short story genre by providing examples of short stories. The teacher explains the material for writing short stories, which includes the characteristics of each short story genre, writing styles, elements that differentiate each genre, and steps for writing short stories.